Level of knowledge about radioprotection, risks and benefits of ionizing radiation in Dentistry students - Salas Bedoya, Elard Daniel (2024)
Objective: To determine the level of knowledge about radiological protection, risks and benefits of the use of ionizing radiation in undergraduate students of Dentistry at a Peruvian university. Materials and methods: Cross-sectional study, where participants completed a validated survey on a scale from 0 to 20. The results were statistically analyzed using Fisher's exact test and the chi-square test. Results: The level of knowledge of 90.67% (n = 68) of the students was intermediate. Regarding radiation protection, 77.33% (n = 58) have an intermediate level of knowledge; regarding risks, 53.33% (n = 40) have a low level; and, regarding radiation benefits, 50.67% (n = 38) have an intermediate level. Conclusions: Undergraduate students have an intermediate level of knowledge in radiological protection, risks, and benefits of radiation. There was no significant evidence of statistical association between the level of knowledge and the variables sex and continuity of the academic program.